"I'm just here to enjoy the Ponies": My Little Pony, Bronies and the limits of feminist intent. (3rd April 2022) - Hunting, Kyra; Hains, Rebecca C.
ABSTRACT: The unexpected adult, primarily male, audience of the children's series My Little Pony: Friendship is Magic, known as Bronies, has been the subject of extensive commentary for their apparent violation of gender norms. Drawing from a qualitative survey of a 2915 Bronies we argue that the fandom is deceptively heterogenous. In particular, we explore the attitudes of members of the Brony Fandom to the feminist messages of the series, the feminism of series' creator Lauren Faust, and whether these messages are perceived as impactful. Our paper argues that even within distinctive, close-knit fan communities interpretations interpretive and ideological responses to a media text and context vary significantly. Further, we argue that interpretations of fan objects appears primarily determined by preexisting attitudes. Ultimately, we find that fans utilize a number of rhetorical techniques to reframe media text's messages, producer's intent, and other audience member's responses to fit their preexisting belief systems.